Pentecostal church growth in Nigeria amid Roman Catholicism - Uroko, Favour C. (African Journal of Pentecostal Studies, 2024)
Background: The Roman Catholic Church is believed to have the largest membership. However, the recent growth in Pentecostalism tends to show the strategies that have been adopted by Pentecostal churches in drawing members from the Roman Catholic Church in Nigeria. Although literature has been written on the growth of Pentecostalism in Nigeria, scholars are yet to explain how the growth of Pentecostalism has been influenced by the inflow of Roman Catholic members in Nigeria. Objectives: This article examines how Pentecostal churches draw their membership from the Roman Catholic Church in Nigeria. Method: This study is a qualitative one, with data obtained from secondary literature. This includes journals, textbooks and gazettes. Discourse analysis was used to analyse the data. Results: Findings show that some of the factors that have led to this exchange include: (1) signs, wonders and testimonials; (2) casting out of demons; (3) preaching against poverty; (4) allowing one’s potential to grow, among others. Conclusion: The youth, who seem to be overambitious in exercising their talents, seem comfortable with the model that Pentecostal churches provide for self-exhortation and manifestation. This has sustained the upsurge in the number of youths combining both Roman Catholicism and Pentecostalism in Nigeria. Contribution: The absence of a focus on the prosperity gospel, exorcism of demons, and the presentation of miraculous signs and wonders through publicly broadcasted testimonies within the Roman Catholic Church were found to provide Pentecostal churches with a distinct advantage in attracting members.